Enhancing Financial Institution Operations Through Data-Driven Decision-Making (Journal of Namibian Studies : History Politics Culture, 2023)
The significance of data-driven decision-making (DDD) procedures in banking is the focus of this study. Institutions are increasingly relying on data-driven strategies to enhance their decision-making abilities in the modern, fast-paced, and cutthroat financial industry. An investigation of DDD practices inside financial institutions, such as banks, investment firms, and insurance organisations, was conducted, and the main results and insights are summarised in this abstract. Examining how DDD might boost performance, customer satisfaction, operational efficiency, and risk management is the focus of this article. Data quality concerns, organisational culture, and legal compliance are some of the obstacles that are examined in relation to DDD activities. In order for financial institutions to remain competitive and resilient in an ever-changing industry, this research highlights the significance of using data analytics and advanced technologies to make informed decisions. The research uses case studies and empirical evidence to support this claim.